2005
DOI: 10.1042/bj20040738
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4-2 (neural precursor cell expressed, developmentally down-regulated 4-2) negatively regulates TGF-β (transforming growth factor-β) signalling by inducing ubiquitin-mediated degradation of Smad2 and TGF-β type I receptor

Abstract: Inhibitory Smad, Smad7, is a potent inhibitor of TGF-β (transforming growth factor-β) superfamily signalling. By binding to activated type I receptors, it prevents the activation of R-Smads (receptor-regulated Smads). To identify new components of the Smad pathway, we performed yeast two-hybrid screening using Smad7 as bait, and identified NEDD4-2 (neural precursor cell expressed, developmentally down-regulated 4-2) as a direct binding partner of Smad7. NEDD4-2 is structurally similar to Smurfs (Smad ubiquitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
143
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(156 citation statements)
references
References 43 publications
(62 reference statements)
5
143
0
3
Order By: Relevance
“…This effect is due to the ability of Hsp90 to bind and chaperone the receptors. Earlier work has also established that the [32,33]. Both proteins are structurally similar to the Smurfs and also work similarly to promote receptor downregulation, which results in decreased phosphorylation of R-Smads and negative regulation of TGFb-mediated transcription.…”
Section: Regulation Of Tgfβ Receptor Stabilitymentioning
confidence: 92%
“…This effect is due to the ability of Hsp90 to bind and chaperone the receptors. Earlier work has also established that the [32,33]. Both proteins are structurally similar to the Smurfs and also work similarly to promote receptor downregulation, which results in decreased phosphorylation of R-Smads and negative regulation of TGFb-mediated transcription.…”
Section: Regulation Of Tgfβ Receptor Stabilitymentioning
confidence: 92%
“…It has been recently demonstrated that Smad2 and I-Smads can interact not only with WW-HECT domain ligases of the Smurf family, but also with novel related proteins, named WWP1/Tiul1 and NEDD4 -2 (11,12,37). These E3 ligases are larger in size compared with Smurfs and contain more WW domains than Smurfs (Fig.…”
Section: Smurf2 Wwp1 and Nedd4 -2 Mediate Smad4mentioning
confidence: 99%
“…A second WW-HECT domain E3 ligase, Tiul1/WWP1, forms complexes with Smad2 after TGF-␤ stimulation via the Smad2-interacting transcriptional co-repressor TGF-␤-induced factor, and leads to Smad2 polyubiquitination and down-regulation of TGF-␤ signaling (11). Similar to WWP1, another E3 ligase that contains WW and HECT domains, NEDD4 -2, interacts with Smad2 and induces its poly-ubiquitination and degradation (12). In contrast, Smad3 is down-regulated by the Roc1⅐SCF ubiquitin ligase complex (13).…”
mentioning
confidence: 99%
“…Whilst studies concur that WWP1/Tiul1 alone does not induce the degradation of R-Smads, but rather TβRI (see section 7), to negatively regulate TGF-β-signaling [52,53], Seo et al reveal that WWP1/Tiul1 can interact with the TGF-β/Smad transcriptional repressor TGIF to induce ubiquitindependent degradation of Smad2 [53]. Intriguingly NEDD4-2, like Smurf2, was found to bind to Smad2/3 in a ligand dependent manner, but only to induce degradation of Smad2 [54]. Finally, of particular interest, Itch provides a rarer example of how a R-Smad E3 ligase can positively regulate TGF-β signaling, as it appears to enhance Smad2 SXS phosphorylation [55].…”
Section: Regulation Of R-smads By the Ubiquitin-proteasome Pathway Anmentioning
confidence: 99%
“…Thus, this is an interesting situation in which Smad7, and presumably Smad6, undergoes post-translational modification itself, whilst working as an adaptor to enable Smurfs to initiate the ubiquitination of TGF-β superfamily receptors and ultimately the termination of signaling upstream of R-Smads. Like Smad2, TβRI can also be degraded by the Smurf-like proteins NEDD4-2 [54] and WWP1/ Tiul1 [52,53]. Similar to Smurfs, WWP1/Tiul1 associates with Smad7 to induce its nuclear export and enhance Smad7-TβRI association, and thus ubiquitination and degradation of the receptor [52,53].…”
Section: I-smads and T β Rsmentioning
confidence: 99%